ERGONOMICS 4.0: DIGITALIZATION PROBLEMS AND OVERCOMING THEM - Protasenko, О.; Mygal, G. (Municipal economy of cities. Series: «Economy science», 2023)
The article aims to research the impact of digitalization on operator activity. The main concepts and components of the digital environment are considered. The research directions of human-machine interaction in the digital environment are analysed. The problems of digitalization and their impact on the safety and efficiency of the operator's activities are studied. The “Ergonomics 4.0” conception, which combines existing ergonomic trends in the study of the digital environment, creates a single conceptual apparatus and is the basis for developing practical methods for increasing the safety and efficiency of human-machine interaction in the digital environment.